2019
DOI: 10.1017/s096719941800062x
|View full text |Cite
|
Sign up to set email alerts
|

Proteins from male and female reproductive tracts involved in sperm function regulation

Abstract: SummarySpermatogenesis is a dynamic process that culminates in the production of mature spermatozoa in the seminiferous tubules of sexually mature animals. Although sperm leaving the testis are fully differentiated, they must further undergo two additional maturation steps before acquiring the capability to fertilize the egg. Such processes take place during the epididymal residency and transport in the seminal fluid during ejaculation and, after delivery into the female reproductive tract, during the journey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 151 publications
(194 reference statements)
0
13
0
Order By: Relevance
“…Protein tyrosine phosphorylation is a key intracellular signalling event regulating sperm function and is an indicator of capacitation and essential for sperm to correctly undergo acrosome reaction. [25][26][27] Seminal fluid-derived proteins attached to the sperm surface can inhibit the process of capacitation by negatively affecting the hyperactive motility and protein tyrosine phosphorylation [28]. The seminal plasma was in contact with spermatozoa throughout the MS selection, and our results have shown that the protein tyrosine phosphorylation level was affected in the processed fraction; however, the level was significantly higher than that of the DG group.…”
Section: Discussionmentioning
confidence: 52%
“…Protein tyrosine phosphorylation is a key intracellular signalling event regulating sperm function and is an indicator of capacitation and essential for sperm to correctly undergo acrosome reaction. [25][26][27] Seminal fluid-derived proteins attached to the sperm surface can inhibit the process of capacitation by negatively affecting the hyperactive motility and protein tyrosine phosphorylation [28]. The seminal plasma was in contact with spermatozoa throughout the MS selection, and our results have shown that the protein tyrosine phosphorylation level was affected in the processed fraction; however, the level was significantly higher than that of the DG group.…”
Section: Discussionmentioning
confidence: 52%
“…In line with these data, we found that incubation under CAP conditions increased sperm motility, mitochondrial activity, and tyrosine phosphorylation compared to NC conditions. During their journey through the female reproductive tract, sperm interact with different proteins, molecules, and hormones to achieve fertilization [18]. Under in vitro conditions, ram sperm are frequently incubated in a capacitating medium supplemented with estrous sheep serum (ESS) to acquire their fertilizing ability [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors proposed a new viewpoint, where translation of new proteins from mRNA transcripts can take place during sperm capacitation [14,15,16]. Therefore, the acquisition of sperm function and their fertilizing ability depend on post-translational modifications of existing proteins [17], interaction with proteins present in the male and female reproductive tract [18], or probably even on the synthesis of new proteins [19].…”
Section: Introductionmentioning
confidence: 99%
“…The high levels of BSP1 will cause an imbalance in the plasma membrane, so the sperm will be more sensitive during cryopreservation [41], and cause early capacitation of sperm, which will reduce or reduce the cryosurvivability and fertility of the bull [42,43]. Viana et al [44] reported that high BSP5 concentrations are found in high fertility bulls, and this protein is very useful in the process of membrane stability and sperm capacitation, and embryonic development.…”
Section: Plasma Seminal Proteinsmentioning
confidence: 99%